Modification by sex and atopy of the effect of chemical air pollutions and biological air pollutants including pollen and fungal spores on children respiratory health in the Western Cape, Cape South Africa - Mahmoud, Hussein Yasmeen (Department of Public Health and Family Medicine, 2025)
Asthma continues to be a leading cause of morbidity and mortality among children in SubSaharan Africa. Ongoing under-diagnosis and treatment in low-and middle-income countries, together exposure to airborne pollutants and allergens contribute to this disease burden. A cross-sectional study that recruited 590 school children residing in four informal settlements in the Western Cape province was conducted to assess the role of sex and atopic status on the association between air pollutants and childhood asthma. Exposure to NO2 and PM2.5 were estimated for individual homes using a land-use regression model, while pollen and fungal spores were measured using spore traps positioned in each study area during the follow-up study between May 2016 and September 2016. Asthma-related outcomes were obtained using the International Study of Allergy and Asthma in children (ISAAC) questionnaire, spirometry, and fractional exhaled nitric oxide (FeNO) testing. The study found that increased annual grass pollen levels and annual NO2 levels were positively associated with airway obstruction (OR: 2.26, 95% CI: 1.02-5.03) for annual grass pollen and FeNO (OR: 2.43, 95% CI:1.19-4.98) for annual NO2 and (OR: 3.43, 95% CI: 1.07-10.99) for grass pollen. Furthermore, there was evidence of effect modification by sex and atopy since associations were much stronger among boys and atopic children. Annual NO2 levels were positively associated with FeNO>35ppb among boys (OR:2.77, 95% CI: 1.02-7.47) but not girls. A strong positive association was also observed between higher annual grass pollen levels and FEV1< LLN in atopic children (OR: 4.46, 95% CI: 1.28-15.59). The study provides evidence that sex and atopy modify the association between annual long-term exposure to grass pollen and NO2 and asthma-related outcomes in children